Green synthesis of hierarchical ZSM-5 using cellulose nanocrystal-mesoporogen at low temperature for catalytic cracking of palm oil into aromatic-rich gasoline - Deaul Aulia; Ainul Maghfirah; Grandprix T.M. Kadja (Results in Engineering)
Catalytic cracking of palm oil into biofuels has been actively studied to minimize our dependence on non-renewable fossil-based energy. In this process, the catalyst holds a key role in determining the cracking efficiency and selectivity. Hierarchical ZSM-5 has shown promising performances in converting palm oil into aromatic-rich gasoline. However, the preparation of hierarchical zeolite often involves highly toxic organic compounds as the mesopore directing agents (mesoporogens). Herein, hierarchical ZSM-5 was prepared assisted by a green mesoporogen, cellulose nanocrystal (CNC), at low temperatures. The addition of CNC in the synthesis process resulted in higher SBET (341–377 m2/g) compared to ZSM-5 prepared without CNC (237 m2/g). Further, the amount of CNC (0, 1, 2, 4 g) significantly influenced the structural properties and catalytic performance of the prepared hierarchical ZSM-5. The TEM analyses show that more mesopore was created as the amount of CNC increased. The hierarchy factors also linearly increased with the increase in the amount of CNC. Overall, the distribution mesopore size of the hierarchical ZSM-5 was in the range of 3–4 nm. Finally, the catalytic test on palm oil revealed better catalytic activity for the prepared hierarchical ZSM-5 than the conventional one by increasing the gasoline yield from 28 to 33 % and the distribution of aromatics in gasoline from 87 to 92 %. Therefore, the prepared CNC-based hierarchical ZSM-5 is a promising catalyst for green gasoline production from palm oil. This study's use of green CNC-mesoporogen and low-temperature synthesis of hierarchical ZSM-5 aligns with sustainability purposes.